Implementation of Using Word Game to Improve Students’ Vocabulary Mastery during Online Learning at the Seventh Graders of Ban Nonsawan School - Fandi Achmad Fauzani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The current study strives to enhance seventh graders’ comprehension of English vocabulary using word games during online learning at Ban Nonsawan School in Loei, Thailand. This study was based on early findings suggesting students have difficulty learning English due to a lack of vocabulary. Participants in this research ranged in age from 12 to 13 years old and were part of a class of 18 students. This study employs a Classroom Action Research (CAR) methodology. The data was gathered by observation, questionnaires, and a test. Triangulation was used to evaluate the data. This study indicates that the seventh-grade students’ junior high school English vocabulary at Ban Nonsawan School, before the classroom action research implemented the word games, averaged 62% in cycle 1. After implementing word games, the score increased in cycle 2, an average of 79%. The results of this study met the achievement indicator of 75%. They show that online learning executing word games can motivate students, remember vocabulary quickly, and make learning fun. Based on the classroom action research findings, it can be concluded that word games can help students in seventh grade at Ban Nonsawan School in Loei, Thailand, enhance their English vocabulary proficiency.